Valorization of phosphogypsum waste through acid geopolymer technology: synthesis, characterization, and environmental assessment. (31st March 2023) - Majdoubi, H.; Makhlouf, R.; Haddaji, Y.; Nadi, M.; Mansouri, S.; Semllal, N.; Oumam, M.; Manoun, B.; Alami, J.; Hannache, H.; Tamraoui, Y.
Highlights: The potential of acidic geopolymer technology in phosphogypsum (PG) waste recovery is well investigated. The incorporation of PG limited the propagation of microcracks and increased the mechanical strength, due to the rod-like microstructure of PG. PG does not contribute to the geopolymerization reaction, and showed a good adhesion with the geopolymer matrix. The heavy metals leaching tests showed that the most of the elaborated samples presented a leaching value lower than the international recommendations. Abstract: Phosphogypsum (PG) constitutes the principal by-product of the phosphate industry which largely restricts its wide development. The incorporation of PG as a reinforcement agent into geopolymer cement, can play however a significant role to enhance their mechanical and microstructural properties and to develop a sustainable geopolymer–PG based circular economy. In this study, geopolymer reinforced PG composites were prepared at different PG content according to PG/MK ratio in the range of 0–1. The mechanical properties of the composites were tested under compressive and flexural strength. The results show a significant enhancement of compressive and flexural strength from 40.14 MPa to 48.43 MPa and 5.13 MPa to 9.1 MPa respectively with addition of 20.6 % and 77.3 % compared standalone geopolymer. This improvement was linked systematically with crack self-healing mechanism due to PG rod-like morphology and its high adhesion to the geopolymer matrix. The heavy metals leaching test show that most of the developed acidic geopolymer– PG composites have a leaching value lower than the international recommendations. Thus, geopolymer– PG composites can constitute an efficient and sustainable alternative to conventional building materials and can be extended to divers' industrial applications.